Brain atrophy and lesion load predict long term disability in multiple sclerosis. Issue 10 (23rd March 2013) - Popescu, Veronica; Agosta, Federica; Hulst, Hanneke E; Sluimer, Ingrid C; Knol, Dirk L; Sormani, Maria Pia; Enzinger, Christian; Ropele, Stefan; Alonso, Julio; Sastre-Garriga, Jaume; Rovira, Alex; Montalban, Xavier; et al.
Abstract : Objective: To determine whether brain atrophy and lesion volumes predict subsequent 10 year clinical evolution in multiple sclerosis (MS). Design: From eight MAGNIMS (MAGNetic resonance Imaging in MS) centres, we retrospectively included 261 MS patients with MR imaging at baseline and after 1–2 years, and Expanded Disability Status Scale (EDSS) scoring at baseline and after 10 years. Annualised whole brain atrophy, central brain atrophy rates and T2 lesion volumes were calculated. Patients were categorised by baseline diagnosis as primary progressive MS (n=77), clinically isolated syndromes (n=18), relapsing–remitting MS (n=97) and secondary progressive MS (n=69). Relapse onset patients were classified as minimally impaired (EDSS=0–3.5, n=111) or moderately impaired (EDSS=4–6, n=55) according to their baseline disability (and regardless of disease type). Linear regression models tested whether whole brain and central atrophy, lesion volumes at baseline, follow-up and lesion volume change predicted 10 year EDSS and MS Severity Scale scores. Results: In the whole patient group, whole brain and central atrophy predicted EDSS at 10 years, corrected for imaging protocol, baseline EDSS and disease modifying treatment. The combined model with central atrophy and lesion volume change as MRI predictors predicted 10 year EDSS with R 2 =0.74 in the whole group and R 2 =0.72 in the relapse onset group. In subgroups, central atrophy was predictive in the minimally impaired relapse onset patients (R 2 =0.68), lesion volumes in moderately impaired relapse onset patients (R 2 =0.21) and whole brain atrophy in primary progressive MS (R 2 =0.34). Conclusions: This large multicentre study points to the complementary predictive value of atrophy and lesion volumes for predicting long term disability in MS.